Use of the Significant Caries Index in quantifying the changes in caries in Switzerland from 1964 to 2000 - Marthaler T, Menghini G, Steiner M. (Blackwell Synergy, 2005)
To follow the changes in the Significant Caries Index (SiC) and the DMFT during the period 1964–2000 in children aged 12 and 15 in the Canton of Zurich.